Master electrician's review - Richard E. Loyd (Thomson/Delmar Learning, 2005)
The success-proven Master Electrician's Review has been greatly expanded and updated based on the 2005 edition of the National Electrical Code to provide journeyman electricians with a clear-cut route to acquiring all of the knowledge and professional expertise they need to become licensed master electricians. New, realistic practice exams, plus a math refresher to update readers' skills in working with fractions, decimals, square roots and powers, are just the beginning. Each easy-to-understand chapter in this concise, yet comprehensive, study guide invites the reader to examine a specific topic on the master electrician licensing exam in detail-from general wiring methods and branch circuits through special conditions and communications systems! Each chapter also contains a large number of questions - styled like those that appear on actual exams - to guide readers quickly and efficiently to mastery of the content The Master Electrician's Review study guide is a "must" when preparing for licensing exams as well as a long-lasting reference that can be used to solve the challenges of today's most complex electrical installations